Quantitative MRI measurements of the Achilles tendon in spondyloarthritis using ultrashort echo times. - Hodgson, R; Menon, N; Grainger, A; O'Connor, P; McGonagle, D; Helliwell, P; Emery, P; Robson, M (2012)
OBJECTIVES: Tendon involvement is common in spondyloarthritis. The MRI signal from the Achilles tendon has been used to quantify mechanical tendinopathy; however, conventional MRI is limited by the short T(2) of normal tendon. Short and ultrashort echo time (UTE) MRI have the potential to better measure signal intensity reflecting changes in T(2) or gadolinium enhancement. Furthermore, UTE images could be used for normalisation to reduce variability. The aim of this work was to investigate such techniques in patients with spondyloarthritis (SpA). METHODS: The Achilles tendons of 14 healthy volunteers and 24 patients with symptomatic spondyloarthritis were studied. Combined UTE (TE=0.07 ms) and gradient echo (TE=4.9 ms) images were acquired before and after intravenous gadolinium together with pre-contrast gradient echo images (TE=2 ms). The signal intensity from a region of interest in the Achilles tendon above the calcaneus was measured. The relative enhancement at echo times of 0.07 ms (RE(0.1)) and 4.9 ms (RE(5)) were calculated. The ratios of the signal intensities from both 4.9 ms and 2 ms gradient echo images to the signal intensity from the UTE image were calculated (RTE(5) and RTE(2) respectively). RESULTS: Interobserver intraclass correlation coefficients were excellent (≥0.97). The contrast-to-noise ratio was higher for enhancement on UTE images than on gradient echo images. RE(0.1), RTE(5) and RTE(2) were significantly higher in SpA patients than controls. CONCLUSION: Signal intensity ratios using UTE images allow quantitative measurements to be made which are sensitive to tendon T(2) or contrast enhancement and which are increased in spondyloarthritis. They therefore have the potential for use as measures of tendon disease in spondyloarthritis.